Online Shopping Decisions Based Perceived Ease of Use As Mediation - Sirda Sirda; Ihwan Susila; Moechammad Nasir; Soepatini Soepatini (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2024)
This research aims to analyze the influence of consumer lifestyles and product knowledge mediated by perceived ease of use on online shopping decisions among online shopping consumers in Sukoharjo using quantitative research methods and SMART PLS 4 analysis tools. The population in this study is online shopping consumers in Sukoharjo district using a non-probability sampling technique through a purposive sampling approach with a sample size of 153 according to the criteria. The results of this research show that Consumer Lifestyles and Perceived Ease of Use have a positive and significant influence on Online Shopping Decisions, while Product Knowledge does not have a significant influence on Online Shopping Decisions, Consumer Lifestyles and Product Knowledge have a positive and significant influence on Online Shopping Decisions which is mediated by Perceived Ease of Use.